Multiple sclerosis and COVID-19 - Mares, Jan; Hartung, Hans-Peter (Biomedical papers, 2020)
This paper reviews currently available data on the novel coronavirus and clinical features of COVID-19, followed by a detailed section on possible modifications of immunomodulatory therapy in multiple sclerosis patients with COVID-19, based on what we know so far. There are discussed: (i) The COVID-19 disease (Epidemiological background SARS-CoV-1 coronavirus; Autoimmune response to COVID-19; Asymptomatic course; SARS-CoV-2 test; COVID-19 symptoms), (ii) Treatment of COVID-19 (Experimental plasma treatment; Antiviral therapy; Antimalarial treatment scheme; Biological treatment; Corticosteroid treatment; Symptomatic treatment; Vaccine preparation) and (iii) Multiple sclerosis and SARS-CoV-2 infection (Epidemiological recommendation).
Keywords: coronavirus; COVID-19; multiple sclerosis; immunomodulatory therapy